Pendampingan dan Bimbingan Teknis Penggunaan Media Pembelajaran D’Volleyball Learning Application Bagi Guru PJOK di Kabupaten Ogan Ilir - Destriani, Destriani; Yusfi, Herri; Destriana, Destriana; Agung Nanda, Fitri; Aryanti, Silvi; Richard Victorian, Ahmad; Saputra, Dandi; Mujahidin, Amirul (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The learning media that was developed in 2022, initially in the form of an application called "D'Volleyball Learning Application" which could only be accessed by downloading it from the Play Store, in 2023 the application developed and can be accessed without downloading it from the Play Store using the web, which can be accessed through the web https://dvolleyball.penjasapps.com/. This website contains features such as written theoretical review features of basic techniques in volleyball, movement phases made with a sequence of movement images for each basic technique, as well as video features that will explain basic techniques in volleyball. The objectives of this activity are: 1) to provide technical assistance and guidance on the use of web-based learning media "D'volleyball learning application" to Physical Education, Sports and Health (PJOK) teachers in Ogan Ilir district, 2) to increase the digital literacy capacity of PJOK teachers in terms of integrating technology in learning activities, 3) to encourage innovation and the latest updates on the modernization of PJOK learning, and 4) to optimize research results in 2023 so that they can be of direct benefit to the community, such as teachers and students. The relationship with SDG's (Sustainable Development Goals) namely SDG 4- Quality education, namely in terms of improving the quality of education by utilizing learning technology. Community service partners are SMP PJOK teachers who are members of the MGMP of Ogan Ilir district. The methods used are mentoring, lectures, questions and answers, and demonstrations. Data collection techniques use questionnaires distributed through Google forms and distributed during training. This community service activity provides a deep understanding of PJOK teachers in using web-based learning media. This understanding can be implemented by PJOK teachers in their respective schools.